Orbital Perivenous Abscess Complicating the Diagnosis and Management of Orbital Cellulitis. Issue 6 (November 2017) - Verma, Rohan; Lee, Bradford W.; Alameddine, Ramzi M.; Ko, Audrey C.; Khanna, Paritosh C.; Kikkawa, Don O.; Korn, Bobby S.
Abstract : An 11-year-old female presented with orbital cellulitis, bacterial sinusitis, enlarged left superior ophthalmic vein, dural venous sinuses, and internal jugular vein. The patient underwent endoscopic sinus surgery and was started on intravenous antibiotics and anticoagulation with limited improvement in orbital signs and symptoms. A magnetic resonance imaging/magnetic resonance venography of the orbits and brain revealed a dilated left superior ophthalmic vein with absence of flow but no clearly discernible orbital abscess. Intravenous corticosteroids resulted in dramatic improvement of pain, hypoglobus, proptosis, and extraocular motility, all of which rapidly recurred on discontinuation. Serial imaging revealed progression of what eventually manifested as a well-defined, rim-enhancing peri-superior ophthalmic vein abscess, which was incised and drained with prompt resolution of orbital cellulitis and complete visual recovery. Abstract : An enlarged superior ophthalmic vein in pediatric orbital cellulitis may be a contraindication to initiating steroids despite a low CRP level and overall systemic improvement.